Positions of the Russian universities in the world university rankings in 2022 - Yu. N. Ebzeeva; Yu. B. Smirnova (RUDN journal of Sociology, 2022)
Many states have been striving to ensure their universities’ presence in the global rankings which reflect not only the significance of universities but also the ‘international prestige of the country’ [11]. The reason for the popularization of global rankings in Russia was the globalization of the Russian system of higher education. Rankings present universities not only to applicants, students and the academic community, but also to potential employers - by informing about the quality of education, research activities, etc. Another significant parameter of global rankings is the ‘information openness’ of universities [11]. In addition, universities are fighting not only for applicants but also for additional funding, since education and science have become an element of the economic exchange [5]. The article considers the positions of the Russian higher education institutions in the world rankings in 2022. The relevance of the study is determined by the current trends in the university scientific research and by the political situation. The ranking system is based on the objective assessment by experts from different countries of the significant achievements of universities. Since the scientific research in Russian universities faces difficulties, the authors argue that global rankings have become a controversial means for assessing the competitiveness of Russian universities. The authors describe the dynamics of the positions of Russian universities in world rankings in 2022, the state of national rankings and the difficulties of scientific research based on the statistical and comparative approaches. The results of the study make a certain contribution to the theory of management and can contribute to the successful promotion of Russian scientific achievements and universities in the world community.